Isolation, phenotypic characterization and genotypic identification of Salmonella species isolated from food and water samples in Karachi, Pakistan - Amber, Memuna; Mohd Esah, Effarizah; Ali Meerani, Zulfiqar; Abbas, Tanveer (International Journal of Endorsing Health Science Research, 2021)
Background: Foodborne illness is a global health problem, and Salmonella is one of the leading bacterial pathogens to cause salmonellosis and typhoid fever worldwide. These infections remain an obstinate risk to human and animal health despite substantial innovations and cleanliness practices. The high incidence of these infections is resulting not only from infected eggs and chicken but also from different food commodities. This research was designed in the direction of the certainties mentioned above and the high occurrence rate of extensively drug-resistant (XDR) infections in Pakistan. Methodology: The study focused on the isolation and identification of Salmonella species from food and water samples collected from different regions of Karachi, Pakistan. The standard protocol of enrichment, culturing, and biochemical confirmation from Biological Analytical Manual (BAM) was used to characterize Salmonella's phenotypic isolation and characterization. These isolates were then subjected to Polymerase chain reaction (PCR) and resolved on 1.5% agarose via electrophoresis. Results: From the total of 1010 samples, 10 genotypically confirmed Salmonella isolates were obtained by detecting the invA gene by using PCR. Food items of different kinds exhibited 80% of the total positive isolates, while 20% is from the water sample. Conclusion: The study exhibited the highest prevalence of Salmonella in chicken meat, which may indicate insufficient hygiene and sanitation practices during slaughtering and the supply chain. Incidence of Salmonella was also found in water and spices, signifying the improper sanitary systems and unhygienic handling of food items in many localities of the city, affecting human health.